2002
DOI: 10.1128/jcm.40.12.4691-4699.2002
|View full text |Cite
|
Sign up to set email alerts
|

Limited Diversity among Human Isolates of Bartonella henselae

Abstract: A study of 59 isolates of Bartonella henselae reveals relatively limited diversity among those of human origin (n ‫؍‬ 28). Either of two distinct alleles of both gltA and 16S ribosomal DNA (rDNA) was found in all isolates, with a high level of congruity between 16S and gltA inheritance among proven human pathogens. Human isolates from all over Eastern Australia were most commonly 16S rDNA (Bergmans) type I, with the same gltA allele as the type strain (Houston-1). Comparable feline isolates were more commonly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
48
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 31 publications
4
48
2
Order By: Relevance
“…Such a higher genetic diversity of B. henselae is as yet unexplained, despite the studies conducted on the relationship between cat and human isolates. In Germany and The Netherlands, a majority of human isolates were of 16S rRNA gene type I whereas cat isolates mostly belonged to type II (3,4,10,28,30). In contrast, in Switzerland, France, and the United States, investigators have demonstrated that most of the human isolates of B. henselae belonged to 16S rRNA gene type II (5,8,17).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such a higher genetic diversity of B. henselae is as yet unexplained, despite the studies conducted on the relationship between cat and human isolates. In Germany and The Netherlands, a majority of human isolates were of 16S rRNA gene type I whereas cat isolates mostly belonged to type II (3,4,10,28,30). In contrast, in Switzerland, France, and the United States, investigators have demonstrated that most of the human isolates of B. henselae belonged to 16S rRNA gene type II (5,8,17).…”
Section: Discussionmentioning
confidence: 99%
“…This method distinguished seven genotypes among 37 human and cat isolates and suggested that lateral gene transfer occurs among B. henselae isolates (21). Although these investigators and others suggested that human infection is caused by a limited number of specific B. henselae genotypes (4,10,21), the discriminatory power of the genotyping methods that they used and the small number of B. henselae isolates that they studied were insufficient to allow any statistically significant conclusions to be drawn. Therefore, a genotyping tool with greater discriminatory power for genotyping B. henselae at the strain level is needed to investigate the diversity and population structure of this bacterium.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…A recent report of the presence of B. henselae DNA in the teeth of cats buried in France between the XIIIth and XVIth Centuries indicated the presence of mainly genotype Houston I whereas in present times genotype Marseille is highly predominant in cats in that country [142]. It is also interesting to note that some reports [16,68] have emphasized that B. henselae genotype Houston was more commonly identified in human cases of CSD whereas genotype Marseille was predominantly isolated within the respective cat populations.…”
Section: Dispersal Of Bartonellae Around the Worldmentioning
confidence: 99%
“…Bartonella and Q fever serology followed by special staining, PCR techniques, and tissue culture may greatly increase diagnostic yield for culture-negative endocarditis (16), but cross-reactivity occurs between bartonellae, chlamydiae, and the Q fever agent (Coxiella burnetii), another important cause of culture-negative endocarditis (25). In addition, serodiagnosis based on the detection of antibodies to Houston 1 antigens in many countries, including Australia (11), may not reliably detect Marseille-type strains (10), which include proven human pathogens in Oceania (9,19). A recent follow-up study from Israel involving outer membrane preparations of the same strain used in our IFAT (ATCC 49793, a typical Houston-like strain) showed that immunoglobulin Mspecific antibody detection in an enzyme immunoassay was especially highly specific in 98 cases of proven cat scratch disease (31), but the serotype specificity of this assay also remains an open question.…”
mentioning
confidence: 99%